Use of sulfonamides in layers in Kampala district, Uganda and sulfonamide residues in commercial eggs - Sasanya, James Jacob (Makerere Medical School, 2005)
BACKGROUND: Use of antimicrobials like sulfonamides in production of layers is a public health risk since it inevitably results in sulfonamide residues in eggs. The presence of the residues may be influenced by knowledge, attitudes and practices of farmers regarding use of sulfonamides (and other antimicrobials) in poultry. OBJECTIVE: The study aimed at assessing the possible contribution of the knowledge, attitudes and practices of poultry farmers to the presence/levels of sulfonamide residues in hen eggs. METHODS: A descriptive cross sectional study was done in the 5 political divisions (and surroundings) of Kampala district. Sixty farmers were systematically sampled from a list of poultry farmers in Kampala and a semi-structured questionnaire administered. Each farmer provided sixty eggs for analysis of sulfadiazine and sulfamethazine residues. Whole eggs were homogenized in acetonitrile and centrifuged twice, extracts evaporated and residues dissolved in mobile phase (32:68, methanol: potassium dihydrogen phosphate). Fats were removed using hexane while anhydrous sodium chloride was added to break emulsions. Extracts were analyzed by reverse phase high performance liquid chromatography with photodiode array detector. RESULTS: Ninety-five percent of the farmers never observed withdrawal periods although 80% of them knew the importance of withdrawal periods. However, farmers noted that they play a great role in ensuring a safe food supply. Most farmers attributed the non-observance of withdrawal periods to poverty and fear to lose their investments. Ninety-eight percent of the samples had detectable levels of the sulfonamides. Meanwhile, 98.3% of the samples that had detectable sulfonamide residues came from farmers who applied antimicrobials in feeds/ water. CONCLUSION: Consumers of hen eggs in Kampala district are at high risk of sulfonamide residue exposure due to poor farming/regulatory practices.